Duration and Risk Assessments in Capital Budgeting. - Blocher, Edward; Stickney, Clyde (The Accounting Review, 1979)
ABSTRACT: This paper brings to the accounting literature the results of recent research from other disciplines on a measure called duration and examines its potential usefulness in capital budgeting decisions. Duration is defined as the number of periods which elapse before the average present value dollar is received from a stream of cash flows. In this paper, the authors define duration and describe its major attributes. Its potential for assessing the risk of changes in required rates of return and the risk of illiquidity are then explored in a capital budgeting setting.